Simulasi Hidrolik Perubahan Desain Bangunan Pengambilan Bendungan Jragung Kabupaten Semarang - Ramlan; Wahyudi, Imam; Setiyawan, Prabowo (Universitas Veteran Bangun Nusantara, 2024)
In a pipe network system, the design of the intake building plays an important role in determining the efficiency of water flow and distribution. Suboptimal designs can cause significant Pressure Losses, uneven flow distribution, and potential damage to infrastructure. This research aims to simulate and analyze the effect of design changes in the Jragung Dam intake building in Semarang Regency on its hydraulic performance. The Jragung Dam is one of the important infrastructures that supports water resource management in the region. In this research, WaterCad hydraulic simulation software was used to model water flow and hydraulic behavior in intake buildings. Hydraulic modeling based on current topographic, hydrological and engineering data of intake structures. Design changes are simulated to evaluate the differences in terms of flow capacity, pressure, and structural stability. The simulation results are then compared with the performance of the initial design with the design due to changes in the reservoir. The results of the research show that there is a change in the position of the reservoir with the minimum water level of the reservoir remaining at an elevation of +93,00, the outlet pressure for the raw water transmission pipe decreases to 1.97 mH2O, while the pressure in the other channels shows relatively small changes with a value of 33.48 respectively. mH2O, 11.34 mH2O, and 34.05 mH2O. These results indicate that the water pressure in the raw water transmission pipe is below the required standard (0.5-8 atm). To overcome energy losses in the raw water transmission line so that water can flow by gravity, the pipe diameter was changed from 900 mm to 1100 mm along 3,469 m. This modification produces an outlet pressure of 10.20 mH2O at the reservoir's minimum water level.